2015
DOI: 10.1016/j.joca.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral bone turnover, but not bone volume, is increased in early stage osteoarthritic lesions in the human hip joint

Abstract: In human end-stage hip OA, BV and bone turnover correlate with the degree of local cartilage degeneration. Subarticular bone sclerosis was only present in regions corresponding to end-stage OA. However, in regions with only none to mild cartilage degeneration the underlying bone had significantly higher turnover in OA patients compared to the control group, suggesting that high bone turnover may contribute to the early pathogenesis of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 44 publications
5
55
0
2
Order By: Relevance
“…We further demonstrated that osteoclast number also increased in p21 −/− mice. Previous studies suggested that a thickening of the subchondral bone plate occurs as a primary fundamental change in subchondral bone in OA, and another study demonstrated that thinning of the subchondral bone occurred before cartilage destruction . These studies suggested that subchondral bone plays a critical role in OA progression.…”
Section: Discussionmentioning
confidence: 91%
“…We further demonstrated that osteoclast number also increased in p21 −/− mice. Previous studies suggested that a thickening of the subchondral bone plate occurs as a primary fundamental change in subchondral bone in OA, and another study demonstrated that thinning of the subchondral bone occurred before cartilage destruction . These studies suggested that subchondral bone plays a critical role in OA progression.…”
Section: Discussionmentioning
confidence: 91%
“…Some studies have previously suggested that a thickening of the growth plate is occurring as a primary fundamental subchondral bone change in OA (147). It has also been demonstrated in animal studies that thinning of the subchondral bone occurred before cartilage damage was detected, suggesting that bone turnover may be increased in the early stages of OA (148). Surely, changes to subchondral bone in the progressive stages of OA are characterized by extensive remodeling of the trabeculae, formation of new bone below new cartilage (osteophytes), and the development of subchondral bone cysts (SBC) (149)(150)(151).…”
Section: Subchondral Bone Changes In Oamentioning
confidence: 97%
“…7,8 The presence and extent of facet joint OA associate with LBP, independent from disc height narrowing, in elderly individuals. 9 Enhanced subchondral bone turnover is a key pathomechanism in idiopathic OA of the hip 10 and knee 11 and leads to subchondral bone sclerosis in advanced disease stages. Pharmacological inhibition of subchondral bone remodeling or surgical restoration of joint biomechanics can revert subchondral bone sclerosis and have demonstrated clinical efficacy in OA.…”
mentioning
confidence: 99%